Survival Rates in Elderly Patients on Continuous Ambulatory Peritoneal Dialysis - Nguyen B; Bui QTH; Tran PQ (International Journal of Nephrology and Renovascular Disease, 2023)
Bach Nguyen,1 Quynh Thi Huong Bui,2,3 Phuong Que Tran2 1Department of Nephrology, Thong Nhat Hospital, Ho Chi Minh City, Vietnam; 2Department of Clinical Pharmacy, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 3Department of Pharmacy, Thong Nhat Hospital, Ho Chi Minh City, VietnamCorrespondence: Bach Nguyen, Department of Nephrology, Thong Nhat Hospital, 1 Ly Thuong Kiet Street, Tan Binh District, Ho Chi Minh City, 700000, Vietnam, Tel +84 28 918209808, Fax +84 28 3865 6715, Email nguyenbach69@gmail.comPurpose: The present study aimed at evaluating the survival rate, its associated factors, and the causes of death in elderly patients undergoing continuous ambulatory peritoneal dialysis (CAPD) in Vietnam.Patients and Methods: This is a retrospective, observational study conducted among patients aged ≥ 65 years who underwent CAPD at Thong Nhat Hospital, Ho Chi Minh City, Vietnam, from April 2012 to December 2020. The Kaplan–Meier method was used to calculate the cumulative survival rate, and the Log rank test was used to analyze the factors associated with the survival rate of patients.Results: This study enrolled a total of 68 patients with a mean age of 71.93 ± 7.44 years at the initiation of CAPD. The most common complication among kidney failure patients was diabetic nephropathy (39.71%). The rate of concomitant cardiovascular diseases was 58.82%. The average survival rate was 45.59 ± 4.01 months. Peritonitis was the most common factor causing death (31.25%), followed by cardiovascular diseases (28.12%) and malnutrition (25%). The factors that impacted the survival rate included concomitant cardiovascular diseases, low serum albumin (< 35 g/dL), and an indication of CAPD due to exhausted vascular access for hemodialysis at baseline. The main factor associated with a shorter survival time was concomitant cardiovascular diseases.Conclusion: It is necessary to improve the survival time beyond 5 years for elderly patients undergoing CAPD, especially for those with concomitant cardiovascular diseases. Besides the prevention of peritonitis, adequate measures to protect from cardiovascular diseases and malnutrition will reduce the mortality rate in patients on CAPD.Keywords: CAPD, elderly, Vietnamese, concomitant diseases, cardiovascular diseases